Assessment of Soybean Resistance to Leaf-feeding Insect, Spodoptera litura - Krisnawati, Ayda; Nuryati, Nuryati; Adie, Mochammad Muchlish (Biosaintifika: Journal of Biology & Biology Education, 2021)
One of soybean problem in Indonesia is leaf damage caused by the Spodoptera litura. The aim of the study was to identify the resistance of soybean genotypes againts army worm based on the preference index and morphophysiological characters. 150 soybean genotypes were grown under field condition from February to May 2018 in Malang (East Java, Indonesia). The preference test was conducted in the laboratory using G100H as resistant reference plant to armyworm. The result showed that the preference index was ranged from 0.09-1.82. A total of 105 genotypes showed a low preference index (resistant), 39 genotypes showed a high preference index (susceptible), and a genotype has similar preference index with the reference plant (has equal resistance with G100H). Based on the preference index and morphophysiological characters, 150 soybean genotypes can be grouped into eight clusters. A genotype from cluster VIII (Anjasmoro/Rajabasa-41) has characteristics of low leaf water content, dense leaf trichomes, and the preference index of 0.14. Those characteristics could be the attributes of the soybean genotypes that is resistant to S. litura. The Anjasmoro/Rajabasa-41 was recommended to be cultivated in Indonesian, or may be used as a gene source in the breeding program for S. litura resistance